USE OF COVER CROPS AND PRE-EMERGENCE HERBICIDES AS WEED MANAGEMENT OPTION IN CONTINUOUS MAIZE (Zea mays L.) PRODUCTION IN IBADAN, NIGERIA (2013)
Crop Rotation (CR) and planting of Cover Crops (CC) are important methods of weed management for sustainable crop production.These and various other methods are usually integrated to enhance weed management in crop production. While reports abound on integrated weed management involving these and other practices, there is inadequate information on integrated use of Pre-emergence Herbicides (PH), CC, and CR in maize production. Therefore, effects of continuous use of CC with PH were evaluated in Ibadan for maize production. Hundred, 75, 50 and 25% of the recommended rates of maize-based PH (atrazine, atrazine+ metolaclor® and metolaclor®) were evaluated on the performance of Cowpea (α), Melon (β), Pumpkin (γ) and “Akidi” (Vigna unguiculata sub-sp sesquipedalis) (θ).The densities of 10,000 and 20,000 plants/ha for γ and α/β/θ respectively were integrated with the effective minimum dose of the PH and evaluated on weed control and maize performance. The appropriate sequence of the CC complemented with hoe-weeding at four Weeks After Sowing (WAS) for weed suppression in intensive maize cropping over four cropping cycles in two years was also evaluated in randomized complete block design. The CC sequences were combinations of any of γ/βand θ/α in early and late seasons (βθγα/βαγθ/γθβα/γαβθ) and continuous sole CC (ββββ/θθθθ/γγγγ/αααα) over four cropping cycles. The controls in each case were three hoe-weedings and unweeded maize plots. Data collected on emergence and Dry Matter Yields (DMY) of the CC, Ground Coverage (GC) of CC,Weed Density (WD), weed biomass at 8 WAS and Maize Grain Yield (MGY) were analysed using descriptive statistics and ANOVA at p=0.05.